Estimation and Influencing Factor Analysis of Carbon Emissions From the Entire Production Cycle for Household consumption: Evidence From the Urban Communities in Beijing, China - Wang, Jiabin; Hui, Wenjie; Liu, Lian; Bai, Yuping; Du, Yudong; Li, Jiajin (Frontiers in Environmental Science, 2022)
Household carbon emissions (HCEs) in urban communities are significant sources of China’s total carbon emissions and contribute to global warming and climate change dramatically. This study aims to estimate the HCEs and investigate their influential factors based on a total of 185 household survey data collected from three typical types of urban communities in Beijing: traditional communities, unit communities, and commercial housing communities with the application of the consumer lifestyle approach (CLA) analysis and econometrics model. The results show that unit communities contribute to the highest direct carbon emissions and the commercial housing communities produce the most indirect carbon emissions, with the traditional communities emitting the lowest carbon emissions both directly and indirectly. The highest direct carbon emissions of households are found in unit communities at 723.79 kgCO2 per month, followed by commercial communities at 580.01 kgCO2, and finally the traditional communities with 526.44 kgCO2 direct carbon emissions monthly. And the highest monthly indirect carbon emissions of households are found in commercial communities at 707.70 kgCO2, followed by unit communities at 669.38 kgCO2, and finally with 554.85 kgCO2 indirect carbon emissions monthly in traditional communities. It concludes that the community type affects HCEs characteristics and their driving factors significantly. Household income, household population, and the ownership of cars increase household carbon emission in more than one type of community. Scientific research work-related population, community environment satisfaction, housing area have positive effects, while community convenience has negative impacts on HCEs in one certain type of community. Policy implications tailored to general and specific community types are proposed as the guidance of carbon reduction and community transformation finally. This study contributes to the understanding of the impact of community attributes on household carbon emissions and proposes some methods for micro-regional carbon emission reduction and the ecological transformation of urban communities.